High-Throughput of Polymer Derived Carbon Nanopillar Arrays for Enhanced Energy Storage Performance. Issue 1761 (23rd July 2015) - Yu, Zenan; Duong, Binh; Moore, Julian; Chantharasupawong, Panit; Li, Chao; Thomas, Jayan
ABSTRACT: Polyacrylonitrile (PAN) was printed into a nanostructured carbon nanopillar arrays using a quick, simple, and highly efficient method called spin-on nanoprinting (SNAP). The mold used to print PAN nanostructures could easily be reproduced via printing an inverse replica of carbon nanopillar arrays. The as-printed carbon nanopillar arrays were further prepared as supercapacitor electrodes. As a result, these nanostructured carbon electrodes display an order of magnitude enhancement in specific capacitance compared to non-nanostructured carbon electrodes.